Extraction of oil from microalgae for biodiesel production: A review - Halim, R.; Danquah, Michael; Webley, P. (2012)
The rapid increase of CO2 concentration in the atmosphere combined with depleted supplies of fossil fuels has led to an increased commercial interest in renewable fuels. Due to their high biomass productivity, rapid lipid accumulation, and ability to survive in saline water, microalgae have been identified as promising feedstocks for industrial-scale production of carbon-neutral biodiesel. This study examines the principles involved in lipid extraction from microalgal cells, a crucial downstream processing step in the production of microalgal biodiesel. We analyze the different technological options currently available for laboratory-scale microalgal lipid extraction, with a primary focus on the prospect of organic solvent and supercritical fluid extraction. The study also provides an assessment of recent breakthroughs in this rapidly developing field and reports on the suitability of microalgal lipid compositions for biodiesel conversion.